Landscape geoecology in the feasibility of creating linear parks in urban microbains - de Moraes, Weslei Reghini; Zacharias, Andréa Aparecida [UNESP]; Oliveira-Costa, Jorge Luis P. (Elsevier, 2024)
The article presents the landscape geoecology in the availability of linear parks creation, in urban microbasins, from the study carried out in Furnas stream, located in the municipality of Ourinhos, State of São Paulo, Brazil, whose Master Plan, to guarantee the environmental equity policies, presents such commitments in Articles 17 and 23. Based on Rodriguez (1994) proposal, a classic in the triad—landscape x planning x urban—the work brings methodological paths for linear parks creation, with concrete actions under a synthesis inventory, based on systemic analysis, from where it was possible to present the diagnosis of the environmental state of the studied urban stream, which has the proposal for linear urban parks implementation by the current municipal master plan. The obtained results can be observed by thematic mapping and systematic field visits, from present environmental processes more detailed analysis; besides Cartographic Sketch, simulating the Proposed Linear Park, elaborated with base on the inventory of the Geoecological Function; Potential Use Capacity; the Socioeconomic and Cultural Function; the Relationship between Potential Capacity and Socioeconomic Function; the Environmental Issue; as well as the Geoecological Environmental State, which classifies the urban landscape as optimized, altered or exhausted.
Keywords: Landscape; Linear parks; Planning; Systemic analysis